PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Teddy Marliadi Nurwan (Journal Of Regional Public Administration (JRPA), 2017)
Research in Cimalaka District, Sumedang Regency, To obtain an assessment of work in  the Cimalaka District  Office,  Sumedang  Regency,  To  obtain  information  about motivation by working together in the Cimalaka District Office, Sumedang Regency, to be enjoyed. working in the Cimalaka District Office of Sumedang Regency. Participating in this study were all Cimalaka District Sumedang District employees who gathered 35 employees. In this study the authors used a saturated sample technique, because the study sample was relatively small at 35 people, so that all studies were sampled. In this study the authors used a saturated sample technique, because the study sample was relatively small at 35 people, so that all studies were sampled. Motivation in Cimalaka Subdistrict, Sumedang Regency has not run well seen in the respondents' answers on average by 51.80%. Employee work productivity in Cimalaka Sub-District, Sumedang Regency has not yet achieved good results because the research reached an average of 52.79%. The correlation between motivation and employee productivity in Cimalaka Sub-District, Sumedang District, the coefficient value is  0.94  depending  on  the category  of  very  strong  and  significant  related  to  the strong relationship   between   Motivation   and   employee   workforce   in   Cimalaka   Sub-district, Sumedang  District.  The  influence  of  motivation  on  employee  productivity  in  Cimalaka District reached 88.36%. the remaining 11.64% is influenced by other factors such as the quality  factor  of  Human  Resources  (HR),   internal  communication,   supervision  and leadership and others.